Brain alpha‐amylase: a novel energy regulator important in Alzheimer disease? - Byman, Elin; Schultz, Nina; Fex, Malin; Wennström, Malin (Brain pathology (Zurich, Switzerland), 2018)
Reduced glucose metabolism and formation of polyglucosan bodies (PGB) are, beside amyloid beta plaques and neurofibrillary tangles, well‐known pathological findings associated with Alzheimer's disease (AD). Since both glucose availability and PGB are regulated by enzymatic degradation of glycogen, we hypothesize that dysfunctional glycogen degradation is a critical event in AD progression. We therefore investigated whether alpha (α)‐amylase, an enzyme known to efficiently degrade polysaccharides in the gastrointestinal tract, is expressed in the hippocampal CA1/subiculum and if the expression is altered in AD patients. Using immunohistochemical staining techniques, we show the presence of the α‐amylase isotypes AMY1A and AMY2A in neuronal dendritic spines, pericytes and astrocytes. Moreover, AD patients showed reduced gene expression of α‐amylase, but conversely increased protein levels of α‐amylase as well as increased activity of the enzyme compared with non‐demented controls. Lastly, we observed increased, albeit not significant, load of periodic acid‐Schiff positive PGB in the brain of AD patients, which correlated with increased α‐amylase activity. These findings show that α‐amylase is expressed and active in the human brain, and suggest the enzyme to be affected, alternatively play a role, in the neurodegenerative Alzheimer's disease pathology.